2011
DOI: 10.1088/1742-6596/273/1/012118
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic order in the filled skutteruditesRPt4Ge12(R= Nd, Eu)

Abstract: Rare-earth metal filled skutterudites RPt4Ge12 with R=La-Nd, and Eu exhibit a variety of different ground states, e.g., conventional and unconventional superconductivity in LaPt4Ge12 and PrPt4Ge12, respectively, and intermediate valence behavior in CePt4Ge12. In this work we investigate the magnetic state of NdPt4Ge12 and EuPt4Ge12 by specific heat, dc-susceptibility and magnetization. NdPt4Ge12 shows two magnetic phase transitions at TN1 = 0.67 K and TN2 = 0.58 K, while EuPt4Ge12 displays a complex magnetic p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 15 publications
3
21
0
Order By: Relevance
“…Filled skutterudites based on rare-earth metals and group 8 transition elements show diverse and interesting rare-earth magnetism, and they have been widely studied (see, for example, refs 28,29,31). To generally survey the magnetic properties for our new filled group 9-based skutterudites, the magnetizations of all the rare-earth-based filled skutterudites were measured from 2 to 200 K with an applied magnetic field of m 0 H ¼ 1 Tesla.…”
Section: A B X a B Xmentioning
confidence: 99%
See 1 more Smart Citation
“…Filled skutterudites based on rare-earth metals and group 8 transition elements show diverse and interesting rare-earth magnetism, and they have been widely studied (see, for example, refs 28,29,31). To generally survey the magnetic properties for our new filled group 9-based skutterudites, the magnetizations of all the rare-earth-based filled skutterudites were measured from 2 to 200 K with an applied magnetic field of m 0 H ¼ 1 Tesla.…”
Section: A B X a B Xmentioning
confidence: 99%
“…Because they make very good thermoelectrics 21,22,47 , host unusual metalinsulator transitions [23][24][25] , can be rare-earth magnets, heavyfermion compounds [26][27][28][29][30] , non-Fermi liquids [31][32][33][34][35] , itinerant ferromagnets [36][37][38] and superconductors 27,[39][40][41][42][43][44][45][46] , and have been proposed as topological insulators 48 , filled skutterudites are a very important class of non-molecular solids. Because the electronic and magnetic properties of solids depend critically on the actual atoms making up the compounds in addition to the compound's electron count, expanding the filled skutterudites from primarily group 8 to group 9 metal-based compounds, as we have done in this study, affords the opportunity to observe many new physical properties.…”
mentioning
confidence: 99%
“…Several M Pt 4 Ge 12 compounds (M = Sr, Ba, La, Pr, Th) become superconductors with T c up to 8.3 K [6]. For M = Nd, Eu a well-localized nature of 4f electrons is observed [11] while SmPt 4 Ge 12 features a heavyfermion state at low temperatures [8]. Theoretical and spectroscopic studies have shown that states at the Fermi level (E F ) can be attributed mainly to Ge 4p electrons while Pt 5d states are lying rather deep and only partially form covalent bonds with Ge 4p [12,13].…”
mentioning
confidence: 99%
“…In particular, the substi-tution of Pr by Ce leads to the suppression of T c with the nodal gap being gradually suppressed [10]. On the other hand, EuPt 4 Ge 12 orders antiferromagnetically [11,12] with a fairly large magnetic moment corresponding to a total angular momentum (J = S = 7/2) and a Neel temperature T N = 1.78 K [13]. Furthermore, the C el vs T curve shows at least three peaks close to the antiferromagnetic transition [13].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, EuPt 4 Ge 12 orders antiferromagnetically [11,12] with a fairly large magnetic moment corresponding to a total angular momentum (J = S = 7/2) and a Neel temperature T N = 1.78 K [13]. Furthermore, the C el vs T curve shows at least three peaks close to the antiferromagnetic transition [13]. For the purposes of the present work, it is important to mention that the heat capacity (C) measurements of Eu-or Gd-containing samples have revealed a low temperature T upturn in C/T as a function of temperature, which has been attributed to a Schottky anomaly resulting from the splitting of the ground state octet of Eu/Gd due to the internal molecular and external applied fields [14][15][16].…”
Section: Introductionmentioning
confidence: 99%